SPECTROSCOPIC STUDIES OF THE CHEMICAL NATURE AND INTERACTION WITH COLLAGEN OF MODIFIED FATLIQUOR MATERIALS - ЗАЄЦЬ, А. В.; АНДРЕЄВА, О. А. (Technologies and Engineering, 2024)
The purpose of the researches is to analyze the chemical nature of new commercial modified fatliquor materials obtained on the basis of sulfonated, sulfated, oxidized natural and synthetic fats, as well as to determine the features of interaction in the "collagen-fatliquor material" system, which will make it possible to predict the behavior of these materials during liquid finishing of leather. Methodology. To achieve this goal, spectral analysis and interpretation of the spectra of modified fatliquor materials were used. As the latter, new products from Smit & Zoon (Netherlands) were studied: Sulphirol EG 60 – sulfited natural and synthetic fats; Synthol LC – natural and synthetic fats, sulfated triglycerides, lecithin-containing mixture; Sulphirol C – oxidized sulfited fats based on marine fish fats. The chemical nature of the analyzed fats and their interaction with gelatin as a collagen model was studied using infrared spectroscopy. The researches were carried out on an infrared spectrometer (FTIR), designed to obtain infrared transmission or reflection spectra of the objects under study. Findings. It has been experimentally established that, due to the presence of various functional groups and bonds, new modified fatliquor materials have a multifunctional nature and can interact with gelatin to form new (hydrogen, electrovalent, covalent, etc.) bonds in its structure. Based on a study of the relative optical density of chrome-plated gelatin films before and after treatment with modified fatliquor materials, it was revealed that sulfur- and phosphorus-containing groups of fats and nitrogen-containing (amine, imine, amide) groups of gelatin take the greatest part in this interaction, its oxygen-containing groups (hydroxyl and carbonyl) are less active) groups. Sulphirol EG 60 sulfited fat and sulfated lecithin-containing Synthol LC exhibit greater activity in interaction with gelatin among the studied fatliquor materials than Sulphirol C fatliquor material synthesized on the basis of oxidized and sulfited marine fish fats. The revealed ability of modified fatliquor materials to interact with gelatin, and therefore with collagen, will contribute to the prevention of their redistribution in the dermis or their removal from it, which will have a positive effect on the stability of the structure and properties of skin and leather products. Originality. The scientific novelty consists in determining the chemical nature of new modified fatliquor materials of various origins, intended for skin treatment, as well as the nature of their interaction with gelatin - a model of collagen, which is the main component of the dermis of the animal skin and natural leather, which is made from it. This will make it possible to explain the peculiarities of transformations in the "collagen-fatliquor material" system during liquid finishing, their influence on the formation of the structure and properties of the leather. Practical value. The results of the work will contribute to the expansion of the assortment and justified use of chemical reagents of the new generation in innovative technologies for the production of leather of the modern assortment.